Equisetum in Malaysia - Yahaya, Mahani; Kiew, Ruth (Malaysian Nature Society, 1982)
Equisetum is represented by a single species, E. ramosissimum Desf. subsp. debile (Roxb.) Hauke in Malaysia. At Gunung Ulu Kali, Pahang, it grows on acid, nutrient poor soil by the roadside. Its growth and cone production is not seasonal and cones are produced on stems about 2--3 years old. The green spores require1ight for germination and germinate within 24 hours. On Knop's agar 50% germination is achieved within 2-3 days and almost 90% after 7 days. Gametophytes were not found at Ulu Kali. The literature for this subspecies is discussed.